Implementation of real-time learning on homomorphically encrypted visual inputs - Bhuiyan, Emtiaz MD Tafsir; Rahman, Mushfiqur; Mondal, Sudipta; Warech, Sadman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.